KNEE WRAPS ARE DETRIMENTAL TO THE MAXIMAL SQUAT PERFORMANCE OF POWERLIFTERS COMPETING IN LOWER WEIGHT CLASSES (Kinesiology, 2023)
The aim of the study was to evaluate the efficacy of knee wraps for competitive powerlifters. To achieve this, an analysis of powerlifting results dating back to 1964 has been conducted. From these results the one repetition max (1RM) squat was evaluated, specifically examining the influence of competitors using knee wraps versus raw (allowing only neoprene knee sleeves). Student’s t-test was used to compare the 1RM squat for male raw competitors (n=270,268) to those using wraps (n=26,576); and likewise for female raw (n=136,530) versus wraps (n=11,468). Overall, the males using wraps yielded significantly higher (p